Hubungan Hukum Para Pihak dalam Peer to Peer Lending - Ratna Hartanto; Juliyani Purnama Ramli (Jurnal Hukum IUS QUIA IUSTUM, 2018)
The development of digital world has provided various services that are beneficial for the community, one of which is the presence of information technology-based lending and borrowing services or known as peer to peer lending. However, the current applicable regulations have not clearly explained the construction of the legal relations among the parties involved in peer to peer lending platform. Regarding the fact that some peer to peer lending services are similar to those of banks, the Financial Services Authority (OJK) is required to affirm the construction of the legal relations among parties so as to create legal certainty. Based on this explanation, there is a question: how is the Legal Relation among the Parties involved in Peer To Peer Lending in terms of the Legal Certainty for these Parties. This study used a normative method. The results showed that peer to peer lending services providers are not banks that collect funds from the community and distribute them to the community. Therefore, the legal relation among the parties involved in peer to peer lending shall be differentiated from the legal relations among the parties involved in banking sector, especially in the business activities of distributing funds through credit or financing agreements. The legal certainty in peer to peer lending shall be fulfilled so that peer to peer lending business activities are not categorized as an illegal bank and so that this business is able to provide legal standing for all the parties.